2015
DOI: 10.1111/dom.12416
|View full text |Cite
|
Sign up to set email alerts
|

Low within‐ and between‐day variability in exposure to new insulin glargine 300 U/ml

Abstract: AimsTo characterize the variability in exposure and metabolic effect of insulin glargine 300 U/ml (Gla-300) at steady state in people with type 1 diabetes (T1DM).MethodsA total of 50 participants with T1DM underwent two 24-h euglycaemic clamps in steady-state conditions after six once-daily administrations of 0.4 U/kg Gla-300 in a double-blind, randomized, two-treatment, two-period, crossover clamp study. Participants were randomized to receive Gla-300 as a standard cartridge formulation in the first treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
115
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(129 citation statements)
references
References 17 publications
7
115
0
7
Order By: Relevance
“…2), resulting in a retarded and prolonged dissolution from the subcutaneous tissue compared with generally available standard glargine (U100) ( Tables 1 and 2). Also, its metabolic degradation to the metabolites M1 (GlyA21 insulin) and M2 (GlyA21, des-ThrB30) is similar to that of insulin glargine U100 (42). These metabolites show binding characteristics to the insulin receptor and IGF-1 receptor comparable with human insulin.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…2), resulting in a retarded and prolonged dissolution from the subcutaneous tissue compared with generally available standard glargine (U100) ( Tables 1 and 2). Also, its metabolic degradation to the metabolites M1 (GlyA21 insulin) and M2 (GlyA21, des-ThrB30) is similar to that of insulin glargine U100 (42). These metabolites show binding characteristics to the insulin receptor and IGF-1 receptor comparable with human insulin.…”
mentioning
confidence: 82%
“…The findings from the DEVOTE study in 7,500 high-risk individuals with type 2 diabetes will be invaluable owing to its prospective, double-blind design. Glargine U300 is a new higherstrength formulation of insulin glargine at 300 IU/mL rather than the usual glargine at 100 IU/mL, which alters its pharmacokinetic and pharmacodynamic properties (1,3,4,22,25,26,41,42). Glargine U300 forms a more compact subcutaneous depot with its surface area reduced by half and its volume by two-thirds (Fig.…”
mentioning
confidence: 99%
“…19,20 Within-subject variability was lower with IGlarU300 than previously reported with IGlarU100. 21,22 Data from phase III clinical trials (EDITION) have shown that IGlarU300 results in a distinct pharmacokinetic and pharmacodynamic profile. It also has a longer duration of action and variability is much less than for IGlarU100.…”
Section: Studies On U300 Insulinmentioning
confidence: 99%
“…In pharmacokinetics and pharmacodynamics studies, insulin glargine 300 U/mL (Gla-300) has demonstrated low variability in exposure over 24 h, a more consistent activity profile, and prolonged maintenance of glucose control compared with insulin glargine 100 U/mL (Gla-100) [8][9][10]. In the randomized, controlled Phase III EDITION clinical trial program, Gla-300 was shown to be non-inferior to Gla-100 in reducing HbA1c levels, without increasing the risk of hypoglycemia versus Gla-100 in patients with type 1 diabetes (T1D) or T2D at 6 months [11][12][13][14] and at 1 year [15,16].…”
Section: Introductionmentioning
confidence: 99%